The effect of organosolv pretreatment variables on enzymatic hydrolysis of sugarcane bagasse - Mesa, Leyanis (2011)
Sugarcane bagasse pretreated with dilute-acid was submitted to an organosolv ethanol process with NaOH under different operational conditions (pretreatment time, temperature, and ethanol concentration) aiming to maximize the glucose yield in the subsequent enzymatic hydrolysis stage. The different pretreatment conditions resulted in variations in the chemical composition of the solid residue as well as in the glucose recovered by enzymatic hydrolysis. All the studied variables presented significant (p < 0.05) influence on the process. The optimum organosolv pretreatment conditions consisted in using 30% (v/v) ethanol at 195 ◦C, during 60 min. Enzymatic hydrolysis of the residue then obtained produced 18.1 g/l glucose, correspondent to a yield of 29.1 g glucose/ 100 g sugarcane bagasse. The scale-up of this process, by performing the acid pretreatment in a 10-l semi-pilot reactor fed with direct steam, was successfully performed, being obtained a glucose yield similar to that found when the acid pretreatment was performed in autoclave.